2002
DOI: 10.1139/t01-062
|View full text |Cite
|
Sign up to set email alerts
|

Strength and dilatancy of a silt stabilized by a cement and fly ash mixture

Abstract: The mechanical behaviour of a weakly cemented silt was studied experimentally. The cementing agent was a cement and fly ash slurry, and the samples so formed were slightly cemented. In triaxial testing, both drained and undrained tests on saturated samples were conducted. Special zero effective stress tests were conducted to measure, directly, the contribution of bonding between grains to the enhanced strength and stiffness. The cemented soils were initially less dilatant than their respective parent soils but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…This indicates a dilatant behaviour at failure. Similar results were reported by Lo and Wardani (2002) for cemented silt.…”
Section: Consolidated Undrained Triaxial Test (Cu)supporting
confidence: 91%
See 1 more Smart Citation
“…This indicates a dilatant behaviour at failure. Similar results were reported by Lo and Wardani (2002) for cemented silt.…”
Section: Consolidated Undrained Triaxial Test (Cu)supporting
confidence: 91%
“…Similar results were obtained by others (Clough et al 1981;Reddy and Saxena 1993). Lo and Wardani (2002) reported that the change in the effective strength parameters of a cemented silt is dependent on the confining pressure. For moderate confining, similar to the one used in the current study, they found that the CSL for cement-treated soil is parallel to that of untreated soil (i.e.…”
Section: Consolidated Undrained Triaxial Test (Cu)supporting
confidence: 89%
“…Chemical stabilizing agents (such as cement, lime, fly ash, gypsum, and other calcium-based materials) have been used extensively for improvement of the soils with poor engineering properties by earlier researchers (Bell, 1996;Lo and Wardani, 2002;Hebib and Farrell, 2003;Sariosseiri and Muhunthan, 2009;Cuisinier et al, 2011;Rahardjo et al, 2013). The engineering behavior of treated soils has been improved dramatically by using these agents.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of cemented soils have been investigated by various authors (Horpibulsuk et al, 2003, Horpibulsuk et al, 2004, Kamon and Bergado, 1991, Kasama et al, 2000, Lo and Wardani. 2002Lorenzo and Bergado.…”
Section: Introductionmentioning
confidence: 99%